IMPLEMENTATION OF THE CONCEPT OF DEVELOPMENT OF PRIVATE HIGHER EDUCATION IN SOCIETY AND ITS CONNECTION WITH THE STRATEGIC DEVELOPMENT OF THE COUNTRY Eshonkulova Nurjakhon (TAMADDUN NURI JURNALI, 2024)
This article presents a scientific and philosophical analysis of the important priorities of higher education reform in the development strategy of the New Uzbekistan, based on such scientific methods as comparative analysis, observation and a systematic approach, issues related to the implementation of the concept of development of non-state higher education in society are investigated.